Biological aspects of the critically endangered fish, Labeo boga in the Ganges River, Northwestern Bangladesh - Md. Yeamin Hossain; Sharmin Jahan; Md. Abu Sayed Jewel; Md. Mosaddequr Rahman; Mst. Monira Khatun; Saleha Jasmine (Universiti Kebangsaan Malaysia, 2015)
The present study reports the first complete and inclusive description of some biological parameters including length-frequency distribution (LFD), sex ratio (SR), length-weight relationship (LWR), condition factors (allometric, KA; Fulton’s, KF; relative, KR and relative weight, WR) and form factor (a3.0) of Labeo boga in the Ganges River, northwestern Bangladesh. Sampling was conducted using traditional fishing gears during April 2011 to March 2012. For each specimen, total length (TL) was measured to the nearest 0.01 cm using digital slide calipers and total body weight (BW) was measured using an electronic balance with 0.01 g accuracy. The LWR was calculated using the expression: W= a Lb, where W is the BW and L is the TL. A total of 211 specimens ranging from 9.78-27.50 cm TL and 10.00 to 276.10 g BW were studied. BW of females was significantly higher than that of males (Mann-Whitney U-test, p>0.001). However the overall sex ratio did not differ significantly from the expected value of 1:1 (χ2 = 0.12, p<0.05). The calculated b for the LWR indicated isometric growth (» 3.00) in males, females and combined gender and there were significant differences in the intercepts but not in the slopes between the sexes of L. boga in the Ganges River. KF of females was significantly higher than that for males (p<0.001). In addition, the Wilcoxon signed rank test showed that the WR did not differ from 100 for males and females in this study indicating good condition of habitat for L. boga. The results of this study would be an effective tool for fishery specialists to initiate early management strategies and regulations for the sustainable management of the remaining stocks of this species within the Padma River and surrounding ecosystems.